Penyidikan Tindak Pidana Pelanggaran Jam Operasional Berdasarkan Peraturan Daerah Kota Pekanbaru Nomor 3 Tahun 2002 Tentang Hiburan Umum - Gaol, Letjan Lumban; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The increasing growth of business activities in the field of public entertainment makesthe government need to conduct control and structuring so that the realization of qualitypublic entertainment services, efficient and more positive impact on the wider community. Inthe investigation stage, it will be determined who becomes the suspect or suspectedperpetrator of a crime. The purpose of writing this thesis, namely: First, to find out theinvestigation of criminal acts against violations of public entertainment operating hoursbased on Pekanbaru City Regulation Number 3 of 2002 Concerning Public Entertainment.Second, to find out the barriers to investigating criminal acts in violation of operating hoursbased on Pekanbaru City Regulation Number 3 of 2002 concerning Public Entertainment.This type of research used in this study is a sociological juridical legal research in theform of research that takes a rigorous approach to the nature of the law and is in accordancewith keyataan in society or the correlation of law with society, so as to be able to reveal theeffectiveness of the law in society and identify the law unwritten that applies to thecommunity, then proceed with research on primary data in the field or in accordance with therealities of life in the community.From the research results, there are two main things that can be concluded. First, theinvestigation of criminal acts against violations of public entertainment operational hoursbased on Pekanbaru City Regulation Number 3 of 2002 Regarding Public Entertainment, hasnot been carried out properly and optimally. This is proven by the fact that there are still alot of public entertainment businesses that violate operational hours in the city of Pekanbaru,but not all of them are carried out in full in accordance with applicable regulations. Second,barriers to investigating criminal acts against operating hours violations based onPekanbaru City Regulation Number 3 of 2002 concerning Public Entertainment. In lawenforcement, there are still many obstacles and obstacles that arise from inside and outsidethe law enforcement agencies which result in the inadequacy of the investigation process inaccordance with applicable law.The author's suggestion, First, is expected to the investigative officer in conductingthe investigation process in accordance with the rule of law and the investigating officer issupported by understanding and equipped with infrastructure. Second, for the sake of thesmooth and upholding of the law in accordance with Pekanbaru City Regulation Number 3 of2002 concerning Public Entertainment, to reduce obstacles in the process of lawenforcement, it is necessary to increase the legal awareness of the public entertainmentbusiness owners and the public by conducting legal socialization conducted by experiencedand insightful officers broad, improve the correlation between relevant agencies withbusiness actors and the wider community for the achievement of legal ideals.Keywords: Education-Operating Hours-General Entertainment-Criminal acts